Competitiveness of Lithuanian Freight Transport Service Sector in the Context of the European Union - Langvinienė, Neringa; Sekliuckienė, Jurgita (Ekonomika, 2007)
Progressive changes, dynamic business environment become a constant of life in several economics spheres, including the Lithuanian freight transport service sector. Lithuanian freight transport services are characterized as sector acting on the terms of high rivalry. The aim of this article is to analyse the competitiveness of the Lithuanian freight transport sector in the context of the European Union. The competitive theoretical background, estimation of competitiveness of freight transport services are analysed. The competitive analysis of the sector through the Porter’s model of five forces and internal characteristics of the enterprise defining the Lithuanian freight transport sector in terms of size and specialization is carried out. The methods of the research are systematics and a comparative analysis of scientific literature, quantitative research based on freight transport organisation survey. An empirical survey in which 349 freight transport service enterprises were examined allowed to reveal and estimate the most important factors influencing the competition intensity and the main firm-level factors that influence the companies’ competitiveness in the economic sector.